Podman for DevOps : containerization reimagined with Podman and its companion tools - Arrichiello, Alessandro; Salinetti, Gianni (Packt Publishing, 2022)
Build, deploy, and manage containers with the next-generation engine and tools Key Features Discover key differences between Docker and Podman Build brand new container images with Buildah, the Podman companion Learn how to manage and integrate containers securely in your existing infrastructure Book Description As containers have become the new de facto standard for packaging applications and their dependencies, understanding how to implement, build, and manage them is now an essential skill for developers, system administrators, and SRE/operations teams. Podman and its companion tools Buildah and Skopeo make a great toolset to boost the development, execution, and management of containerized applications. Starting with the basic concepts of containerization and its underlying technology, this book will help you get your first container up and running with Podman. You'll explore the complete toolkit and go over the development of new containers, their lifecycle management, troubleshooting, and security aspects. Together with Podman, the book illustrates Buildah and Skopeo to complete the tools ecosystem and cover the complete workflow for building, releasing, and managing optimized container images. Podman for DevOps provides a comprehensive view of the full-stack container technology and its relationship with the operating system foundations, along with crucial topics such as networking, monitoring, and integration with systemd, docker-compose, and Kubernetes. By the end of this DevOps book, you'll have developed the skills needed to build and package your applications inside containers as well as to deploy, manage, and integrate them with system services. What you will learn Understand Podman's daemonless approach as a container engine Run, manage, and secure containers with Podman Discover the strategies, concepts, and command-line options for using Buildah to build containers from scratch Manage OCI images with Skopeo Troubleshoot runtime, build, and isolation issues Integrate Podman containers with existing networking and system services Who this book is for The book is for cloud developers looking to learn how to build and package applications inside containers and system administrators who want to deploy, manage, and integrate them with system services and orchestration solutions. This book provides a detailed comparison between Docker and Podman to aid you in learning Podman quickly.